Penerapan etos kerja karyawan terhadap kinerja karyawan di PT. Pos Indonesia Kantor Cabang Utama (KCU) Malang - Afrillia, Fayza (Maliki Interdisciplinary Journal, 2023)
This research aims to determine the application of employee work ethic to employee performance at PT. Pos Indonesia Kantor Cabang Utama (KCU) Malang. This research uses qualitative research methods. Apart from discussing employee work ethic, this article will also highlight the important role of a good work environment in an organization. This research also provides results that work ethic needs to be applied in organizations to achieve organizational goals. The research result explain that work ethic has a prositive and significant impact on employee performance. Employees at PT. Pos Indonesia Kantor Cabang Utama (KCU) still does not fully implement a good work ethic in serving customers and interacting with colleagues. A company can achieve success if it has good facilities and infrastructure, apart from that it is also supported by the work ethic of its employees.